Sense of community in gated and non-gated residential / Siti Rasidah Md Sakip, Noraini Johari and Mohd Najib Mohd Salleh. - Md Sakip, Siti Rasidah; Johari, Noraini; Mohd Salleh, Mohd Najib (Universiti Teknologi MARA Cawangan Selangor, 2018)
Neighbourhood design is one of the factors contributing towards the establishment and maintenance of local community ties. The differences in environmental size and design of neighbourhoods are perceived to influence sense of community networking functions. A physical element such as gated element is also believed to have an influence on local community relationship networking. Therefore, a study on sense of community was conducted in two neighbourhood areas: Putrajaya (non-gated) and Bandar Baru Bangi (gated) using face to face interview method. This study found that residents of nongated residential areas demonstrated higher sense of community (M=6.47 SP=0.08) than residents of gated residential areas (M=6.39, SP=1.08).